Postharvest Life of Gladiolus grandiflorus L. cv. Jessica as Influenced by Pre-harvest Application of Gibberellic Acid and Kinetin - Kumar, Sunil; Gupta, A K (Journal of Postharvest Technology, 2014)
Effect of pre-harvest sprays of gibberellic acid and kinetin on  postharvest life of gladiolus cv. Jessica was assessed. The field  experiment was laid out in randomized block design, replicated  thrice, with two levels of gibberellic acid (100 and 200 ppm) and  kinetin (50 and,100ppm) by dipping the corms overnight and  foliar spray during growth period. The laboratory experiment was  laid out in completely randomized design, replicated thrice, with  sucrose 4 percent and 8-HQC at 200ppm as vase solution to  increase the postharvest life of cut flower. The plant growth  regulators significantly enhanced the postharvest life of cut  gladiolus spike.
Keywords: Gibberellic acid Kinetin; Sucrose; 8-HQC; Vase life